Sliding Windowed Optimization Algorithm for Fusion of Redundant Stereo Visual Odometries - Cabrera-Avila, Elizabeth V.; Silva, Bruno M. F.; Gonçalves, Luiz M. G. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2022: Anais do XIV Simpósio Brasileiro de Robótica e XIX Simpósio Latino Americano de Robótica, 2022)
We propose a sliding windowed graph-optimization based approach for the fusion of two stereo visual odometries with 6 degrees of freedom poses. Stereo odometries are calculated independently, using pairs of stereo images that are captured by stereo cameras mounted on the top of a moving platform. We implemented our sliding windowed approach using the public library LIBVISO2. Our results are compared against the two recognized SLAM frameworks ORB-SLAM2 and UCOSLAM. The relative pose error of the fused poses decreases by up to 94% in relation to the error of single stereo odometry and by up to 91% compared with the results of UCOSLAM.